2008 Eighth IEEE International Conference on Advanced Learning Technologies 2008
DOI: 10.1109/icalt.2008.84
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Learning Styles in Learning Management Systems by Using Indications from Students' Behaviour

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(140 citation statements)
references
References 6 publications
4
127
0
9
Order By: Relevance
“…This paper proposes an advanced student modelling approach which identifies learning styles according to the FSLSM. Investigations are based on previous research work [10], where an automatic and static student modelling approach has been designed, implemented, and evaluated. The evaluation showed that the approach is suitable for identifying learning styles and therefore can be seen as the basis for the development of an advanced student modelling approach which combines automatic, static, dynamic, and global student modelling.…”
Section: Identifying Learning Stylesmentioning
confidence: 99%
“…This paper proposes an advanced student modelling approach which identifies learning styles according to the FSLSM. Investigations are based on previous research work [10], where an automatic and static student modelling approach has been designed, implemented, and evaluated. The evaluation showed that the approach is suitable for identifying learning styles and therefore can be seen as the basis for the development of an advanced student modelling approach which combines automatic, static, dynamic, and global student modelling.…”
Section: Identifying Learning Stylesmentioning
confidence: 99%
“…Montazeri and Ghorbani [13] proposed an Evolutionary Fuzzy Clustering (EFC) methodology with Genetic Algorithm (GA) for the recognition of learning styles of e-learners. The work of Graf et al [14] proposed a literature-based approach that automatically detects the learning styles in LMSs. Dung and Florea [15] tracked data of learners' behaviors and used simple mapping rule to infer learning styles against Felder-Silverman Learning Style Model.…”
Section: A Adaptation Systems To Learner's Learning Stylesmentioning
confidence: 99%
“…x being uncoupled from any Learning Management System (LMS), and independent of students actions in a specific system, as it occurs in traditional approaches, as [16,21];…”
Section: Related Workmentioning
confidence: 99%
“…A diversity of approaches for automatic detection of LS have been proposed, such as [21,20,8]. In general, these traditional approaches use deterministic inference systems for detecting students LS through predefined behavioural patterns.…”
Section: Related Workmentioning
confidence: 99%